2018
DOI: 10.1002/app.46295
|View full text |Cite
|
Sign up to set email alerts
|

GMA‐based emulsion‐templated solid foams: Influence of co‐crosslinker on morphology and mechanical properties

Abstract: Highly open porous polymer foams formed from high internal phase emulsions (polyHIPEs) are attracting significant interest because of their potential applications in many areas of advanced materials science. In this work, the influence of the crosslinker or co-crosslinkers of different molecular weights on the morphology and mechanical properties of polyHIPEs containing glycidyl methacrylate (GMA) was studied. Several poly(ethylene glycol) dimethacrylate (PEGDMA) crosslinkers were considered. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…This diversity in stability could be explained to some extent by the differences in viscosity between the two systems. It has been shown that the stability of an emulsion system increases with an increase in viscosity 10,37 and the uoro-emulsion prepared with PLA showed a higher viscosity compared to the HIPE prepared without PLA. Furthermore, interfacial tension can also promote emulsion stability.…”
Section: Stability Of Hipe and Droplet Size Distributions With And Wimentioning
confidence: 99%
See 4 more Smart Citations
“…This diversity in stability could be explained to some extent by the differences in viscosity between the two systems. It has been shown that the stability of an emulsion system increases with an increase in viscosity 10,37 and the uoro-emulsion prepared with PLA showed a higher viscosity compared to the HIPE prepared without PLA. Furthermore, interfacial tension can also promote emulsion stability.…”
Section: Stability Of Hipe and Droplet Size Distributions With And Wimentioning
confidence: 99%
“…Inspection of the morphology of the porous materials post emulsion polymerization, showed that the average pore sizes of polyHIPE prepared with PLA were smaller than those produced without PLA, consistent with the observed (small) emulsion droplets sizes. The porous material prepared without PLA had the large pore structure of a conventional polyHIPE, 1,10,39 and the average pore diameter was 45.24 mm (Fig. 3A).…”
Section: Stability Of Hipe and Droplet Size Distributions With And Wimentioning
confidence: 99%
See 3 more Smart Citations